An Experimental Study of ZrO2-CeO2 Hybrid Nanofluid and Response Surface Methodology for the Prediction of Heat Transfer Performance: The New Correlations. (20th June 2022) - Vidhya, R.; Balakrishnan, T.; Kumar, B. Suresh; Palanisamy, R.; Panchal, Hitesh; Angulo-Cabanillas, Luis; Shaik, Saboor; Saleh, B.; Alarifi, Ibrahim M.
Abstract : This article experimentally and statistically reports the convective heat transfer performance of a cylindrical mesh-type heat pipe apparatus filled with ZrO2 -CeO2 /water-ethylene glycol nanofluids. In this regard, ZrO2 -CeO2 nanoparticles were synthesized and characterized through the Scanning Electron Microscope and Powder X-ray diffraction methods followed by the preparation of hybrid ZrO2 -CeO2 nanofluids of various concentrations ranging from 0.025 to 0.1%. The heat transfer features of a tubular heat pipe with a mixture of the ZrO2 -CeO2 nanofluid were evaluated. A 5.33% decrease in thermal resistance value and a 41.16% increase in heat transfer ability with increased power input were observed. The potent regression models were proposed to estimate heat transfer features of the heat pipe. The ANOVA statistical method has been employed to determine the P value and the F value of the models towards enhancing the reliability and accuracy of the developed models. The outcome revealed that the proposed models are reliable and have the best fit with the experimental data for 30–60 W power. The correlations' results were validated against the experimental data and showed high accuracy. Moreover, the accuracy of the developed models was ensured through R -squared and adjusted R -squared values.